2007
DOI: 10.1258/095646207782212270
|View full text |Cite
|
Sign up to set email alerts
|

Health providers' competence in the management of reproductive tract infections in Vientiane, Lao People's Democratic Republic

Abstract: This cross-sectional study aimed to assess health providers' reported knowledge and practice competence regarding management of reproductive tract infections (RTIs) including sexually transmitted infections (STIs) in Vientiane, Laos. All 272 health providers (medical doctors/assistants, midwives/nurses and drug sellers) working with RTI/STI patients in one urban and one rural district were invited to fill in a self-completed questionnaire including four written simulated case scenarios, and 93% participated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Another study from Laos found that drugs obtained from pharmacies often have limited efficacy in curing STIs [23]. Moreover, pharmacists/drug sellers have been found to have inadequate knowledge and competence in the management of STI [8,10]. STI training for STI service delivery staff from both the public and the private health sectors is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study from Laos found that drugs obtained from pharmacies often have limited efficacy in curing STIs [23]. Moreover, pharmacists/drug sellers have been found to have inadequate knowledge and competence in the management of STI [8,10]. STI training for STI service delivery staff from both the public and the private health sectors is needed.…”
Section: Discussionmentioning
confidence: 99%
“…In a study from Laos, HCPs, especially in rural areas, reported inadequate knowledge and competencies regarding management of reproductive tract infections (RTIs), including STIs [8]. Owing to the lack of STI clinics and clinical STI specialists, patients with STIs are mainly seen by gynecologists or general health practitioners, often with low competencies in STI management [8]. In addition, self-medication for RTIs including STIs through private pharmacies is common among FSWs in Laos [7].…”
Section: Introductionmentioning
confidence: 99%
“…The final practice competence score as well as knowledge score was then divided into three groups, optimal (≥ 75% of total score), medium (50–74% of total score) and suboptimal (< 50% of total score). These limits have been used as cut-off points in previous studies about knowledge among health personnel [ 20 , 21 ]. A fourth group, very low (< 25%), was later added to distinguish the knowledge level within the suboptimal group.…”
Section: Methodsmentioning
confidence: 99%
“…Improved case management of STI has been scientifically proven to reduce the incidence of HIV infection in the general population [ 3 ],[ 4 ]. In low-income countries, STI management is usually inadequate [ 5 ]-[ 7 ] and STI control programmes often fail for various reasons [ 8 ]. It has been shown that healthcare providers (HCPs) play an important role in reducing the burden of STI through effective prevention and management [ 9 ].…”
Section: Introductionmentioning
confidence: 99%